2013
DOI: 10.1080/10410236.2013.785474
|View full text |Cite
|
Sign up to set email alerts
|

EPPM and Willingness to Respond: The Role of Risk and Efficacy Communication in Strengthening Public Health Emergency Response Systems

Abstract: This study examines the attitudinal impact of an Extended Parallel Process Model (EPPM)-based training curriculum on local public health department (LHD) workers' willingness to respond to representative public health emergency scenarios. Data are from 71 U.S. LHDs in urban and rural settings across nine states. The study explores changes in response willingness and EPPM threat and efficacy appraisals between randomly assigned control versus intervention health departments, at baseline and 1 week post curricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…4,6 This in turn highlights the need for efficacy-focused strategies and interventions to boost response willingness among this occupational cohort. 21 Healthcare providers have a generally accepted duty to treat individuals in need of medical attention. The duty of a healthcare provider to treat an individual in need is based on the provider's expert training and commitment to upholding the professional code of conduct.…”
Section: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…4,6 This in turn highlights the need for efficacy-focused strategies and interventions to boost response willingness among this occupational cohort. 21 Healthcare providers have a generally accepted duty to treat individuals in need of medical attention. The duty of a healthcare provider to treat an individual in need is based on the provider's expert training and commitment to upholding the professional code of conduct.…”
Section: Empirical Evidencementioning
confidence: 99%
“…The presence of such laws provides opportunities for training and other advance preparations for a response among local health departments, improving workers' response-related skills and making them more comfortable with the parameters of their response roles and responsibilities. 21,65 Many elements contribute to legal conceptions of a duty to respond, or report to work, during an infectious disease emergency. As noted above, for members of the public health workforce, a key concern is whether liability protections, beyond those included in the PREP Act relative to countermeasures, will apply to their response efforts.…”
Section: Legal Considerationsmentioning
confidence: 99%
“…Prior research has found that LHD workers’ response willingness increases when their sense of efficacy (i.e., ability to understand and execute their response role) improves. 21 …”
Section: Discussionmentioning
confidence: 99%
“…The higher the score, the stronger the core emergency response capability. Targeted training in response to the lack of emergency capacity can enhance the self-e cacy of medical staff in response to public health emergencies, thereby enhancing their willingness to participate in rescue [16]. Therefore, at the end of the questionnaire, the content of medical staff's self-e cacy was added.…”
Section: Design Of the Surveymentioning
confidence: 99%